Tradisi Hukum Indonesia: Sejarah, Produk Hukum dan Kebijakan di Masa Orde Baru - Jantarda Mauli Hutagalung; Tantri Gloriawati (Jurnal Hukum Sasana, 2022)
Indonesia is one of the countries that considers law as the most important part of state life, apart from politics and the economy. Basically, in a state of law, the government is actually the spearhead of the law as a system. The Indonesian legal system itself is a legal system formed from a long history of acculturation of customs, the entry of Islam and the civil law system brought by the Dutch. This long history has helped shape the Indonesian legal system, which has unique legal and policy products. This paper discusses the characteristics of Indonesian law in terms of the legal concept, apart from the dynamics of the development of the Indonesian legal tradition which is based on the nomadic history of Indonesian society. The results of the discussion show that the Indonesian legal tradition is characterized by respect for the law that lives in society. The Indonesian legal system as whole remains committed to respecting different religions and cultures, moving towards democracy and the rule of law.